Seroprevalence in health care workers during the later phase of the second wave: Results of three hospitals in Serbia, prior to vaccine administration. Issue 7 (July 2022) - Markovic-Denic, Ljiljana; Zdravkovic, Marija; Ercegovac, Marko; Djukic, Vladimir; Nikolic, Vladimir; Cujic, Danica; Micic, Dusan; Pekmezovic, Tatjana; ,; Marusic, Vuk; Popadic, Viseslav; Crnokrak, Bogdan; et al.
Abstract: Background: Since the COVID-19 pandemic has started, Serbia has faced problems in implementing proper public health measures in the population, including non-pharmaceutical interventions, as well as protecting health care workers (HCWs) from disease, like all other countries. This study aimed to estimate COVID-19 seroprevalence and evaluate the risk perception of COVID-19 among HCWs in three different hospitals in Belgrade, Serbia: non-COVID hospital, Emergency Center (EC), and dedicated COVID hospital. Methods: A cross-sectional study was conducted in three hospitals during the second wave of the outbreak in Serbia, from June to early October. All staff in these hospitals were invited to voluntarily participate in blood sampling for IgG antibodies against SARS-CoV-2 and questionnaire testing. The questionnaire included socio-demographic characteristics, known exposure to COVID-19 positive persons, previous signs and symptoms related to COVID-19 infection since the outbreak had started in our country, and SARS-CoV-2 PCR testing. Results: The overall prevalence of SARS-CoV-2 antibody among 1580 HCWs was 18.3 % [95 % CI 16.4–20.3 %]. Significantly higher prevalence of HCWs with positive results for the serum IgG antibody test was observed in COVID hospital (28.6 %, 95 %CI: 24.0–33.6 %) vs. prevalence in the EC (12.6 %, 95 %CI: 10.1–15.4 %), and in the non-COVID hospital (18.3 %, 95 %CI: 15.2–26.7 %). The prevalence adjusted for declared test sensitivity and specificity would be 16.8 %; that is 27.4 % in COVID-19 hospital, 10.9 % in EC, and 16.8 % in non-COVID hospital. In multivariate logistic regression analysis, the independent predictors for seropositivity were working in COVID-hospital, the profession of physician, and the presence of the following symptoms: fever, shortness of breath, and anosmia/ageusia. Conclusions: We found an overall seropositivity rate of 18.3 % and 16.0 % of the adjusted rate that is higher than seroprevalence obtained in similar studies conducted before vaccinations started. The possibility that patients in non-COVID dedicated hospitals might also be infectious, although PCR tested, imposes the need for the use of personal protective equipment also in non-COVID medical institutions.